Particle Adhesion Force Distributions on Rough Surfaces - Götzinger, Martin; Peukert, Wolfgang (Langmuir, 2004)
The effect of roughness on adhesion force distribution was studied in the gas phase. Spherical gold particles with diameters between 5 and 20 μm were generated in a flame process and glued onto atomic force microscope (AFM) cantilevers directly after. Nanostructured substrates with defined roughness were produced by a dip-coating process. The geometry of the adhering partners was determined by AFM imaging, and the adhesion force was measured with the AFM. Depending on the roughness of the particles and the substrates, three types of distribution functions can be identified; two of them can be explained with a simple model. The obtained adhesion force distributions not only agree with those experimentally recorded in previous studies of commercially important powders (e.g., alumina, toner, and gold on different substrates) but also agree with distributions reported in the literature.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.adhesi_9